5-Hydroxymethylcytosine – the elusive epigenetic mark in mammalian DNA - Kriukienė, Edita (2012)
Over the past decade, epigenetic phenomena claimed a central role in cell regulatory processes and proved important factors for understanding complex human diseases. One of the best understood epigenetic mechanisms is DNA methylation. In the mammalian genome, cytosines (C) were long known to exist in two functional states: unmethylated or methylated at the 5-position of the pyrimidine ring (5mC). Recent studies of genomic DNA from the human and mouse brain, neurons and from mouse embryonic stem cells found that a substantial fraction of 5mC in CpG dinucleotides is converted to 5-hydroxymethyl-cytosine (hmC) by the action of 2-oxoglutarate- and Fe(II)-dependent oxygenases of the TET family. These findings provided important clues in a long elusive mechanism of active DNA demethylation and bolstered a fresh wave of studies in the area of epigenetic regulation in mammals. This (15) review is dedicated to critical assessment of the most popular techniques with respect to their suitability for analysis of hmC in mammalian genomes. It also discusses the most recent data on biochemical and chemical aspects of the formation and further conversion of this nucleobase in DNA and its possible biological roles in cell differentiation, embryogenesis and brain function.